Validasi Metode Spektrofotometri UV Penetapan Kadar Tablet Ranitidin HCl dalam HCl - Sefryantonius Lase; Suprianto Suprianto (Jurnal Indah Sains dan Klinis, 2024)
Introduction: Ranitidine HCl tablets are widely available in the market. Ensuring the proper levels of active ingredients is crucial for ensuring the quality of medications. Objective: To find a reliable method for measuring the levels of Ranitidine HCl tablets in acidic solvents that meet validation standards, and to explore valid methods using ultraviolet spectrophotometry in acidic solvents. Methods: UV spectrophotometry with a UV detector at maximum wavelength was used. Two solvents were employed: 0.10 N HCl and 0.15 N HCl. Method validation included tests for linearity, accuracy, repeatability, precision, and selectivity. Results: The maximum wavelengths detected for each solvent were 225 nm and 226 nm, respectively. Validation results indicate excellent linearity, accuracy, and precision within the ranges of 0.9984 - 0.9998; 99.6% - 100.7%; 0.427% - 0.861%; 0.518% - 0.952%. The selectivity test yielded positive outcomes. The average Ranitidine HCl tablet levels were 98.2% for PT. Hexpharm Jaya and 98.4% for PT. Mutifa Medan, meeting the standards of the Indonesian Pharmacopoeia Edition VI. Conclusion: The method using a 0.10 N solvent for determining Ranitidine HCl tablet levels meets validation requirements and is suitable for practical application.